The 10 October 2024 geomagnetic storm may have caused the premature reentry of a Starlink satellite - Oliveira, Denny M.; Zesta, Eftyhia; Nandy, Dibyendu (Frontiers in Astronomy and Space Sciences, 2025)
In this short communication, we qualitatively analyze possible effects of the 10 October 2024 geomagnetic storm on accelerating the reentry of a Starlink satellite from very low-Earth orbit (VLEO). The storm took place near the maximum of solar cycle (SC) 25, which has shown to be more intense than SC24. Based on preliminary geomagnetic indices, the 10 October 2024, along with the 10 May 2024, were the most intense events since the well-known Halloween storms of October/November 2003. By looking at a preliminary version of the Dst index and altitudes along with velocities extracted from two-line element (TLE) data of the Starlink-1089 (SL-1089) satellite, we observe a possible connection between storm main phase onset and a sharp decay of SL-1089. The satellite was predicted to reenter on 22 October, but it reentered on 12 October, 10 days before schedule. The sharp altitude decay of SL-1089 revealed by TLE data coincides with the storm main phase onset. We compare the deorbiting altitudes of another three satellites during different geomagnetic conditions and observe that the day difference between actual and predicted reentries increases for periods with higher geomagnetic activity. Therefore, we call for future research to establish the eventual causal relationship between storm occurrence and satellite orbital decay. As predicted by previous works, SC25 is already producing extreme geomagnetic storms with unprecedented satellite orbital drag effects and consequences for current megaconstellations in VLEO.